2018
DOI: 10.5005/jp-journals-10015-1524
|View full text |Cite
|
Sign up to set email alerts
|

Morindacitrifolia: A Fruit to Future Endodontics

Abstract: The aim of this article is to review Morinda citrifolia in the field of endodontics. Herbal medicaments have been used as remedies for various illnesses and diseases for centuries. Furthermore, it has been a topic of interest in dentistry for many years. Morinda citrifolia juice (MCJ), also commonly known as "Noni," a tropical fruit, has a wide range of uses in endodontics and in the eradication of endodontic pathogens without any potential side effects. A literature review is conducted using electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
0
1
0
Order By: Relevance
“…The botanical name of the commercially available Noni is Morinda citrifolia also known as Indian Mulberry. 26,27 Noni has gained popularity in recent times because of its antibacterial, antiviral, antifungal, antitumor, anti-tubercular effect, analgesic activity, immunological activity. Due to these medicinal properties, it also consumed daily as a supplemental health drink.…”
Section: Noni / Morinda Citrifoliamentioning
confidence: 99%
“…The botanical name of the commercially available Noni is Morinda citrifolia also known as Indian Mulberry. 26,27 Noni has gained popularity in recent times because of its antibacterial, antiviral, antifungal, antitumor, anti-tubercular effect, analgesic activity, immunological activity. Due to these medicinal properties, it also consumed daily as a supplemental health drink.…”
Section: Noni / Morinda Citrifoliamentioning
confidence: 99%
“…Arpornsuwan and Punjanon (2006) showed the growthinhibition of breast cancer and neuroblastoma cell lines in vitro by a methanol extract of the fruits of Morinda L. at a concentration of 0.1 mg/ml. Pharmacological investigations have demonstrated that the roots of Morinda citrifolia possess an antihypertensive action and that an alcoholic extract has an in vitro antispasmodic effect (MOOKHTIAR et al, 2018).…”
Section: Morinda Citrifolia L (Rubiaceae)mentioning
confidence: 99%